Do benefits from dynamic tariffing rise? Welfare effects of real-time pricing under carbon-tax-induced variable renewable energy supply - Christian Gambardella; Michael Pahle; Wolf-Peter Schill (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
Common intuition holds that retail real-time pricing (RTP) of electricity demand should become more beneficial in markets with high variable renewable energy (VRE) supply mainly due to increased price volatility. Using German market data, we test this intuition by simulating long-run electricity market equilibria with carbon-tax-induced VRE investment and real-time price responsive and nonresponsive consumption behavior. We find that the potential welfare gains from RTP are only partially explained by price volatility and are rather driven by opposing wholesale price effects caused by the technology portfolio changes from carbon taxation. Consequently, annual benefits from RTP actually change nonmonotonously with the carbon tax level, implying that increasing RTP at relatively high VRE shares can be both less and much more beneficial than without VRE supply. Nonetheless, as zero marginal cost supply becomes abundant with VRE entry, allocative efficiency increasingly depends on exposing more and more consumers to RTP.
Keywords: 330; Real-time pricing; Electricity; Variable renewables; Carbon taxation; Welfare analysis; Partial equilibrium modeling